Penguatan Keterampilan Psikososial dalam Bimbingan Ketahanan Keluarga bagi Pasangan Pranikah: Studi Di KUA Kecamatan Cianjur - Aisyah Puteri Supriani; Dudy Imanuddin Effendi; Sugandi Miharja (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
This research aims to examine the strengthening of psychosocial skills in the implementation of premarital guidance at the Religious Affairs Office (KUA) of Cianjur District and its relevance in building family resilience. The psychosocial skills studied include effective communication, emotional management, empathy, couple cooperation, and joint decision-making as the foundation of a healthy marital relationship. This research uses a qualitative approach with data collection techniques in the form of in-depth interviews, observation of the implementation of premarital guidance, and analysis of supporting documents. The research results show that the premarital guidance program contributes to increasing the understanding and awareness of participants regarding the importance of psychosocial skills in domestic life, especially in the aspects of healthy communication and cooperation between couples. However, the effectiveness of strengthening these skills is still relatively limited. This is due to the dominance of the lecture method, the lack of direct practice and simulation, and the lack of a long-term guidance and follow-up mechanism after marriage. The positive impact produced is more seen in the cognitive and affective realms of the participants, while the mastery of practical skills and their contribution to sustainable family resilience is not optimal. Based on the findings, this study recommends the development of a premarital guidance model based on practice and experience, increasing the capacity of facilitators in psychosocial approaches, and the implementation of longitudinal evaluations to assess the long-term impact of the program on family resilience. Thus, premarital guidance is expected not only to be informative, but also to be a strategic means in building a harmonious, adaptive, and resilient family.